Paula - Allende, Isabel; Peden, Margaret Sayers (New York : HarperPerennial, 1996)
An autobiography of the life and family of Chilean author, Isabel Allende.
PW
7-A.
7.
Keywords: Allende, Isabel -- Family; Allende family; Allende, Isabel; Allende family; Authors, Chilean -- 20th century -- Family relationships; Chilean authors -- Biography